THE ROLE OF THE THREE MAIN CHARACTERS IN SUPPORTING THE THEME OF TO THE LIGHTHOUSE BY VIRGINIA WOOLF - eny suprihandani (STIBA IEC JAKARTA, 2018)
Virginia Woolf (1882-1941), a brilliant English writer, has been called as a feminist, since she fought for women’s rights and protested the domination of men. She might be also called as an androgynist writer, for she sometimes emphasized the harmony of men and women. To the Lighthouse, which was published in 1927, is her best novel of both feminism and androgyny. It is a realistic novel about a family and an elegy for people Virginia loved. Based on the strong and deep memories of her own family, she described a group of the more complex people spending holiday in a summer house on Scottish coast. It consists of Mr. and Mrs. Ramsay with their eight children and assorted guests. They are going to have a visit to a nearby lighthouse. It is put off because of the weather, and takes place ten years later. From this delay of the expedition to the lighthouse, she constructed the complex tensions of family life and the conflict of male and female principles. For Virginia there is not one of kind of truth, but two. There is the truth of reason, and there is the truth of imagination. The truth of reason is pre-eminently the masculine sphere, while the truth of imagination, or intuitive, is the feminine. Together, these truths make up what she calls reality. Regarding this idea, in To the Lighthouse, she tries to imply a theme about the harmony by presenting male and female characters that have contradictory views and different principles.There are many characters in To the Lighthouse, Mr. Ramsay, Mrs. Ramsay and Lily Briscoe are supposed to be the main characters since they dominantly support the development of the events and even most of the story focuses on their actions, attitudes and thoughts. This research aims to give evidence that Mr. Ramsay, Mrs. Ramsay and Lily Briscoe are all the main characters who, with their words, thoughts and actions, relate each other to support the theme of To the Lighthouse